Measuring time use in developing country agriculture: Evidence from Bangladesh and Uganda - Seymour, Greg; Malapit, Hazel J.; Quisumbing, Agnes R. (Taylor and Francis, 2020)
This paper discusses the challenges associated with implementing time-use surveys among agricultural households in developing countries and offers advice on best practices for two common measurement methods: stylized questions and time diaries. Using data from Women’s Empowerment in Agriculture Index (WEAI) surveys in Bangladesh and Uganda, it finds that stylized questions do not always produce shorter interviews compared to time diaries, and recall accuracy may depend on the regularity and saliency of the activity and enumerator abilities. The paper suggests that combining promising methodological innovations from other disciplines with mainstream time-use data collection methods would allow capture of both the quantity and quality of time and provide richer insights into gendered time-use patterns. Broadening the scope of time-use research to other aspects of well-being can help identify how time constraints contribute to gender inequality and inform the design of policies and interventions to relieve those constraints.